Development of a liquid chromatography-tandem mass spectrometry method for simultaneous detection of the main milk allergens. (April 2017) - Ji, Jian; Zhu, Pei; Pi, Fuwei; Sun, Chao; Sun, Jiadi; Jia, Min; Ying, Chen; Zhang, Yinzhi; Sun, Xiulan
Abstract: The goal of this study is development and validation of a method to confirm and quantify milk allergens in food products based on liquid chromatography-tandem multiple reactions-monitoring, mass spectrometry (LC-MRM/MS). Here, emphasis was placed on two whey proteins, α-lactalbumin (α-La) and β-lactoglobulin (β-Lg), plus a third, αs1 -casein (αs1 -CN), known to be the main allergenic components of milk. Five marker peptides (one for α-La, two for β-Lg and two for αs1 -CN) and three quantitative marker peptides from the digestion of standard milk proteins were identified using matrix-assisted laser desorption/ionization with tandem time-of-flight mass spectrometry (MALDI-TOF/TOF MS). Optimization of enzymatic hydrolysis conditions were defined as 37 °C for 16 h. The linearity ranges for the three allergenic proteins (α-La, β-Lg and αs1 -CN) were 0.97–31.25 μg/mL, 0.48–31.25 μg/mL and 0.48–31.25 μg/mL, respectively. The assays were validated for absolute quantification of three milk proteins with satisfactory results, which indicates that the established mass method is suitable for the expression of levels in daily food. Highlights: A LC-MRM/MS method for simultaneous determination of multi-allergens is proposed. Identification and quantification of marker peptides is the core mechanism. MRM parameter and enzymatic hydrolysis were strictly controlled.